(untitled) (Agro Productividad, 2021)
Objective: To determine potential and water-limited yields in oil palm producing areas in the State of Tabasco, México. Design/Methodology/Approach: The ERIC III v. 3.2 database (IMTA, 2009) was used to select climatological stations with daily precipitation and maximum and minimum temperature records, going back to more than 20 years. The methodology proposed by the FAO and improved by Fischer et al. (2012) was used to estimate the potential yield. The equation reported by Ruiz-Álvarez et al. (2012) was used to estimate the annual water deficit from the climatic water balance. Results: The average potential yield of oil palm with a high level of inputs varies from 35.8 to 40.6 t ha-1 of fresh fruit bunches. The average water-limited yield can vary from 15.6 to 23.5 t ha-1 in plantations of at least 8 years of age, under rainfed conditions. The reduction in the maximum average attainable yield was the result of 19.2-49.5% soil moisture deficits. Study limitations/Implications: In order to determine their impact on potential and water-limited yields, climate change horizons must be included in future studies; this would enable researchers to establish the future theoretical economic profitability of the crop. Findings/Conclusions: The analysis between the yields indicates that —if the gap between the current yields and water-limited yields is closed— output and percentage would be 6.5-14.4 t ha-1 and 72.8-129% higher than the potential yield.